Quantification of arsenic in soil by inductively coupled plasma – Optical emission spectrometry / Vickneswary a/p Letchmanan - Letchmanan, Vickneswary (2014)
In this study, determination of arsenic in soil samples was done by Inductively Coupled Plasma – Optical Emission Spectrometry. Soil from five different locations with three sampling points was collected. The location chosen were garden, dam, beach, construction and agriculture areas. A standard method was used for the sample preparation using HotBlockTM system. The highest arsenic concentrated found in the construction area (32.24 ± 0.02 mg/kg) and followed by agriculture (31.55 ± 0.03 mg/kg), garden (19.17 ± 0.02 mg/kg), dam (17.12 ± 0.01 mg/kg) and beach (1.73 ± 0.01 mg/kg).